2012
DOI: 10.4319/lo.2012.57.1.0305
|View full text |Cite
|
Sign up to set email alerts
|

Identification of senescence and death in Emiliania huxleyi and Thalassiosira pseudonana: Cell staining, chlorophyll alterations, and dimethylsulfoniopropionate (DMSP) metabolism

Abstract: We measured membrane permeability, hydrolytic enzyme, and caspase-like activities using fluorescent cell stains to document changes caused by nutrient exhaustion in the coccolithophore Emiliania huxleyi and the diatom Thalassiosira pseudonana, during batch-culture nutrient limitation. We related these changes to cell death, pigment alteration, and concentrations of dimethylsulfide (DMS) and dimethylsulfoniopropionate (DMSP) to assess the transformation of these compounds as cell physiological condition changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
67
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 55 publications
5
67
0
Order By: Relevance
“…In the upper mixed layer of open oligotrophic oceans, phytoplankton can experience high (dynamic) irradiance conditions in combination with low nutrient availability. It has been suggested that these co-occurring conditions increase photoinhibition and viability loss in natural communities (Lesser et al 1994;Llabrés and Agustí 2006;Franklin et al 2009). However, the present study showed that P. marinus, Ostreococcus sp., and T. oceanica are actually less susceptible to both photoinhibition and viability loss during high-irradiance exposure when nutrient availability is low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the upper mixed layer of open oligotrophic oceans, phytoplankton can experience high (dynamic) irradiance conditions in combination with low nutrient availability. It has been suggested that these co-occurring conditions increase photoinhibition and viability loss in natural communities (Lesser et al 1994;Llabrés and Agustí 2006;Franklin et al 2009). However, the present study showed that P. marinus, Ostreococcus sp., and T. oceanica are actually less susceptible to both photoinhibition and viability loss during high-irradiance exposure when nutrient availability is low.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the direct effect of low-nutrient availability on phytoplankton viability, it may have considerable effects on phytoplankton photophysiology and consequently on the response to high-irradiance intensities. Generally, the lightharvesting capacity is reduced during nutrient starvation by a reduction in the cellular chlorophyll a (Chl a) concentration and quantum yield of PSII, as well as an increase in the relative amount of carotenoids Berges and Falkowski 1998;Franklin et al 2012). However, the absorption of chlorophyll and the absorption cross section of the remaining PSII may increase during nutrient starvation Berges et al 1996), partially counteracting the reduced light-harvesting capacity.…”
mentioning
confidence: 99%
“…Veldhuis et al (2001) hypothesized that 'automortality' is a significant source of DOM leakage, particularly as cells with compromised cell membranes are often still capable of photosynthesis. Subsequent work has shown that stresses such as low irradiance or nutrient limitation affect compromised plasma membranes and autocatalytic cell death in phytoplankton (Berman-Frank et al, 2007;Timmermans et al, 2007;Franklin et al, 2012).…”
Section: Autocatalytic Cell Deathmentioning
confidence: 99%
“…Recent research has shown that phytoplankton also undergo the physiological process of autocatalytic cell-suicide, which can lead to lysis of the cells; this process is analogous to programmed cell death (PCD) in metazoans (Bidle & Falkowski, 2004;Franklin et al, 2006). Autocatalytic cell death is a process that is indicated by multiple changes within the phytoplankton cell and it is often difficult to characterize such cells as clearly dead or alive (Franklin et al, 2006(Franklin et al, , 2012. Cell membrane integrity is used as an early indicator of cell death (Veldhuis et al, 2001).…”
Section: Autocatalytic Cell Deathmentioning
confidence: 99%
“…In previous studies, two types of cyanobacteria have been proposed in terms of pigment and morphological patterns (Jeffrey and Wright, 2006 thiebautii possessed significant amounts of these carotenoids. In the Synechococcus strain, Chl a allomer (i.e., Chl a allo; peak 32) was detected, indicating the oxidation of Chl a by cell senescence (Franklin et al, 2012).…”
Section: Separation and Identification Of Pigments In Phytoplankton Cmentioning
confidence: 99%